Peirce and education: contemporary reflections in the spirit of a contrite fallibilist (Foro de Educacion, 2013)
The author of this essay draws out some of the most important implications of Peirce’s thought for the philosophy of education. In particular, he focuses on the deliberate cultivation of phenomenological attention, methodological (or heuristic) imagination, experiential realism, contrite fallibilism, and wide erudition as implications of Peirce’s texts. Especially in conjunction with phenomenological attention, he develops a notion of world, but a distinctively pragmatic conception of this highly ambiguous word. Then, in connection with this understanding of world, the author makes a case for the pragmatist reconstruction (or reconceptualization) of human experience. While the received view takes experience to be inherently and invincibly subjective, the reconstructed (or pragmatist) one takes experience to be a direct, yet mediated encounter with reality. Peirce’s thought drives in the direction of recognizing, in reference to education, the need for a recovery of the world and the reconstruction of experience. But it also prompts us to see just how important are a resolute fallibilism, heuristic imagination, and wide learning.